Spectrophotometric Determination of Magnesium in Tea - Li, Xiao-Dong; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2013)
The optimum conditions for the spectrophotometric determination of Mg(II) using chlorophosphonazo-III (CPA-III) as chromogenic agent. The present method has been successfully applied to the determination of magnesium in tea samples. In a medium of pH 9.5 NH3-NH4Cl the maximum absorption peak of Mg(II)-(CPA-III) is at 676 nm, at which the apparent molar absorptivity of the method is 1.77 × 104 L mol-1 cm-1 and Beer's law is obeyed over the range of 0-0.48 μg/mL. Its regression equation is: A = 0.9519 C(μg/mL) + 0.0101, with a correlated coefficient of 0.9990. The detection limit of method is 8.92 ng/mL.